Lipid profile in type 2 diabetes mellitus: a case-controlled study - Rajendran, Babu; Mallampati, Seetha Rami Reddy; Jha J., Sheju Jonathan; Hakkim, Shameer (International Journal of Advances in Medicine, 2019)
Background: Atherosclerosis is caused by the combination of type 2 diabetes mellitus and dyslipidemia. Combination of DM and dyslipidemia is associated with increased mortality and morbidity. Hence, it is of utmost importance to know the nature of dyslipidemia in DM for its effective management. The major lipid abnormalities seen in DM are elevated triglyceride levels and lowered HDL-C levels. Methods: A case-controlled study was initiated in Vinayaka Missions Medical college and hospital for a period of 2 year. Pre-prandial and post-prandial lipid profile was assessed in 50 cases of type 2 DM and was compared with age and sex matched healthy controls satisfying the inclusion and exclusion criteria. Results: At the end of the study, the mean age±SD was 48.5±5.68 years. The mean HbA1c±SD of the study population was found to be 7.48±1.517. Looking at the lipid profile all cases in fasting state had elevated VLDL-C levels (mean 50.39±60.27), elevated TC (mean 169.70±39.917), elevated TGL (mean 146.04±60.140) and low LDL-C (mean 92.3±27.699) when compared to control group. In the postprandial state, there was a significant raise in TGL level (mean 188±68.59), raised TC (mean 180.74±38.46), decreased HDL-C (mean 38.761±9.028) compared to the fasting state. Conclusions: Lipid profile of type 2 DM in pre-prandial 12 hour fasting state showed elevated TC, VLDL-C levels and low LDL-C and HDL-C levels. Where as in post prandial state TGL levels were markedly elevated with elevated TC and low HDL-C levels.